PENDAMPINGAN LITERASI FIQH MUAMALAH MALIYAH PADA KOPERASI BUEKA AS-SAKINAH KABUPATEN MALANG - Aprilianto , Fitrian; Hakim, Rahmad (Bulletin of Community Service and Development, 2022)
Purpose of the study: The purpose of this activity is to increase the understanding of the management on the basics of fiqh muamalah in the economic and financial fields. Methodology: The implementation method which refers to the mutually agreed upon situational analysis of the program is discussion, outreach, interactive dialogue, evaluation in two forms, namely in the form of a survey and also in the form of a simulation after the event takes place. Main Findings: There is an increase in understanding regarding the concepts and contracts in fiqh muamalah of Islamic finance for the management of the Bueka As-Sakinah Cooperative, Malang Regency. Applications of this study: This dedication is useful in the application of concepts and contracts in fiqh muamalah Islamic finance at the Bueka As-Sakinah Cooperative, Malang Regency. Novelty/Originality of this study: increased understanding regarding the concept and contracts in fiqh muamalah sharia finance for Cooperative management.